Forging a Socialist Homeland from Multiple Worlds: North American Finns in Soviet Karelia 1921-1938 - Kitty Lam (The Romanian Association for Baltic and Nordic Studies, 2010)
In the early 1930s, the Soviet Union recruited an estimated 6,000 Finns from North America to augment the number of skilled workers in the recently established Karelian Autonomous Republic. Using migrants' letters and memoirs held at the Immigration History Research Center, this essay examines how these North American Finns adapted and responded to fluctuating policies in the Soviet Union that originally flaunted the foreign workers as leaders in the Soviet modernization drive and as the vanguard for exporting revolution, but eventually condemned them as an enemy nation to be expunged. It also analyzes the extent to which these immigrants internalized 'building socialism' as part of their encounter with Soviet Karelia. Such an exploration requires assessing how these settlers’ ideological adaptation affected their experiences. This paper argues that by placing the North American Finns’ experience in the wider context of Soviet state building policies, these migrants’ identity formation involved participation in, avoidance of, and opposition to the terms of daily life that emerged within the purview of building socialism.